2008
DOI: 10.1002/hbm.20706
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable neural effects of stimulus valence and preceding context during the inhibition of responses to emotional faces

Abstract: Socially appropriate behavior requires the concurrent inhibition of actions that are inappropriate in the context. This self-regulatory function requires an interaction of inhibitory and emotional processes that recruits brain regions beyond those engaged by either process alone. In this study, we isolated brain activity associated with response inhibition and emotional processing in 24 healthy adults using event-related functional magnetic resonance imaging (fMRI) and a go/no-go task that independently manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 62 publications
11
78
2
Order By: Relevance
“…Shafritz, Collins and Blumberg (2006) found greater activation in the VLPFC/anterior insula, posterior parietal cortex, ACC and left DLPFC during inhibition of happy and sad emotional faces. Similar results have been described by Hare et al (2008) and Schulz et al (2009) during inhibitory processes involving facial emotional expressions. In another FMRI study performed with happy and sad faces (Vanderhasselt, KĂŒhn & De Raedt, 2011), it has been found that high clinically healthy brooders, who frequently think about negative events, compensate for their difficulty in inhibiting negative information by recruiting more attentional control.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Shafritz, Collins and Blumberg (2006) found greater activation in the VLPFC/anterior insula, posterior parietal cortex, ACC and left DLPFC during inhibition of happy and sad emotional faces. Similar results have been described by Hare et al (2008) and Schulz et al (2009) during inhibitory processes involving facial emotional expressions. In another FMRI study performed with happy and sad faces (Vanderhasselt, KĂŒhn & De Raedt, 2011), it has been found that high clinically healthy brooders, who frequently think about negative events, compensate for their difficulty in inhibiting negative information by recruiting more attentional control.…”
Section: Introductionsupporting
confidence: 89%
“…However, these effects may be related to the interaction of the two networks proposed by Schulz et al (2009) during inhibition of responses to emotional faces: on the one hand, the frontoparietal circuit that exerts inhibitory control; and, on the other, the frontostriatal circuit, which is engaged in the decodification of emotional signals. Another point to be taken into account is the participation of the ACC in emotional valence, as has been described in other studies (Albert et al, 2010;Elliot, Rubitnsztein, et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the function of pars orbitalis, it has been implicated in the semantic processing of language [12][13][14]. Furthermore, although it is thought to be related to inhibitory control [15,16] and motivation [17,18], these are usually associated with activation of both sides. Our study showed that the pars orbitalis was activated bilaterally.…”
Section: Discussionmentioning
confidence: 99%
“…High negative reactivity can inhibit children's attention, cooperative learning, academic motivation, and information recall (Pekrun et al, 2009;Schultz et al, 2009;Perbandt, 2007;Granziano, et al, 2007;Gilliom et al, 2002). Consequently, children with high negative reactivity have difficulty not only acquiring early academic skills but also are at risk for overall academic underachievement (Denham et al, 2012;Newman et al, 1998).…”
Section: Child Temperamentmentioning
confidence: 99%